Analisis Scientific Reasoning Siswa dalam Pembelajaran Fluida Dinamis dengan Model STEM-PjBL - Lorensia, Sinthia Lolita; Handayani, Rif'ati Dina; Lesmono, Albertus Djoko (Universitas Indraprasta PGRI Jakarta, 2024)
Scientific reasoning ability is an important aspect in learning so that students are able to apply the scientific method. In fact, research on students' scientific reasoning is still rare. STEM-PjBL is learning through projects to achieve certain results contextually by mastering several STEM concepts that are currently widely implemented. This research aims to analyze students' scientific reasoning ability in learning physics dynamic fluid material through the implementation of STEM-PJBL. This type of research is descriptive qualitative research with a case study approach carried out at SMAN 4 Jember in the odd semester of the 2023/2024 school year with a research population of one class XI. The subjects in this study amounted to 36 students who were divided into 6 groups. Scientific reasoning ability has six indicators that are measured during the learning process of dynamic fluid through STEM-PjBL. The results of this study indicate that the indicators that are categorized as very good are indicators of probabilistic reasoning and hypothesis-deductive reasoning. Indicators that are categorized as good include indicators of conservation reasoning, proportional reasoning, and correlation reasoning. The indicator that is categorized as very poor is the variable control indicator. This shows that students' scientific reasoning ability can be analyzed with the STEM-PjBL model. With STEM-PjBL, most students' scientific reasoning skills are good. However, it needs to be improved again, especially in the ability to control variables.